Needle electromyography and histopathologic correlation in myopathies. Issue 3 (29th December 2018) - Sener, Ugur; Martinez‐Thompson, Jennifer; Laughlin, Ruple S.; Dimberg, Elliot L.; Rubin, Devon I.
ABSTRACT: Introduction: Needle electromyography (EMG) findings help confirm myopathy and may indicate specific pathologic changes on muscle biopsy. Methods: We conducted a retrospective chart review of 218 consecutive patients referred for muscle biopsy. Presence of specific needle EMG findings was correlated with pathologic findings of inflammation, necrosis, splitting, and vacuolar changes. Sensitivity, specificity, and positive and negative predictive values of specific EMG findings for pathologic changes were calculated. Results: Short‐duration motor unit potentials (MUP) were sensitive (83%–94%) but not specific (34%–49%) for pathologic changes. Fibrillation potentials were 65%–74% sensitive and 58%–81% specific for inflammation, necrosis, splitting, or vacuolar changes. The absence of fibrillation potentials had high negative predictive value (82%–93%) for inflammation, splitting, or vacuolar changes. Discussion: Fibrillation potentials and short‐duration MUPs predict pathologic changes of muscle fiber necrosis, splitting, and/or vacuolar changes (as seen with inflammatory myopathies and muscular dystrophies). Absence of fibrillation potentials suggests other myopathologic changes (e.g., congenital myopathy). Muscle Nerve 59 :315–320, 2019